Pengaruh Model Inkuiri Terbimbing Dipadu Advance Organizer terhadap Peningkatan Kemampuan Berpikir Kritis Siswa pada Materi Gerak Harmonik Sederhana - Mahesti Kusdiastuti; Gunawan Gunawan; Ahmad Harjono; Mir'atun Nisyah (Indonesian Publication Center, 2022)
This study aims to analyze the effect of a guided inquiry learning model combined with advance organizers on enhancing high school students' critical thinking skills in Simple Harmonic Motion (SHM). Utilizing a quasi-experimental design, this quantitative research involved two experimental groups and one control group at senior high schools in Mataram. The experimental groups engaged in guided inquiry learning integrated with concept maps and short videos as advance organizers. Data were collected through pre-tests and post-tests using a five-item essay instrument validated by experts, then analyzed using normalized gain (N-gain). The findings revealed that the critical thinking skills of both experimental groups increased in the high N-gain category, whereas the control group showed a moderate increase. Among the critical thinking indicators,